Criminal responsibility of a juvenile in relation to the provisions of the Criminal Code - Katarzyna Majchrzak (The Francis de Sales Scientific Society (TNFS.PL), 2024)
Under Polish criminal law, a juvenile is a person under the age of 17. In principle, such person would not be liable for the offence under the terms of the Criminal Code. The responsibility of juveniles is extensively regulated in the Act of 9th June 2022 on the Support and Rehabilitation of Juveniles. However, in specific cases, which are explicitly set out in the Criminal Code, a juvenile over the age of 15 or even 14 may be held criminally responsible. Whereby the treatment of a juvenile as an adult and the application of criminal responsibility to him/her requires, in addition to the commission of one of the strictly defined offences, that the circumstances of the case and the degree of development of the offender, his/her personal conditions as well as his/her personal characteristics should also support this. The sentence imposed on a juvenile offender may not exceed 2/3 of the upper limit of the statutory penalty range for the offence in question. The legislature, however, left it to the court's discretion whether it would be advisable to apply extraordinary mitigation in a particular case. Furthermore, a juvenile cannot be sentenced to life imprisonment.